2017
DOI: 10.1371/journal.pone.0178736
|View full text |Cite
|
Sign up to set email alerts
|

Culture, social networks and HIV vulnerability among men who have sex with men in Indonesia

Abstract: The current study aimed to explore cultural and social network influence on HIV vulnerability among Men who have Sex with Men (MSM) population in Yogyakarta, Indonesia. A qualitative inquiry employing in-depth one-on-one interviews was carried out with 24 MSM participants in July 2015. Data were analysed using a framework analysis and guided by the Social Networks Theory (SNT) as a conceptual framework. Findings indicated that prohibitive cultural perspectives and norms against same-sex marriage made them to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 33 publications
(47 reference statements)
9
36
0
2
Order By: Relevance
“…In line with the previous findings reported elsewhere ( Fajans et al, 1994 ; Fauk, Mery, Sigilipoe, Putra, & Mwanri, 2017 ; Ford et al, 2002 ; Hounton et al, 2005 ; Voeten et al, 2002 ; Volk & Koopman, 2001 ; Wulfert et al, 1996 ), the current study depicts a positive relationship between barriers, including feeling uncomfortable while using condoms, decreased sexual pleasure, low satisfaction and sexual sensation, unavailability of condoms immediately before the use, and inconsistent or lack of condom use among participants. Factors such as high prices of condoms, not knowing the places to access or buy condoms, feeling ashamed or uncomfortable to access or buy condoms, as well as unawareness of the existence of condoms and their protective functions were also barriers to condom use or safe sex behaviors reported among the clients of FCSWs.…”
Section: Discussionsupporting
confidence: 92%
“…In line with the previous findings reported elsewhere ( Fajans et al, 1994 ; Fauk, Mery, Sigilipoe, Putra, & Mwanri, 2017 ; Ford et al, 2002 ; Hounton et al, 2005 ; Voeten et al, 2002 ; Volk & Koopman, 2001 ; Wulfert et al, 1996 ), the current study depicts a positive relationship between barriers, including feeling uncomfortable while using condoms, decreased sexual pleasure, low satisfaction and sexual sensation, unavailability of condoms immediately before the use, and inconsistent or lack of condom use among participants. Factors such as high prices of condoms, not knowing the places to access or buy condoms, feeling ashamed or uncomfortable to access or buy condoms, as well as unawareness of the existence of condoms and their protective functions were also barriers to condom use or safe sex behaviors reported among the clients of FCSWs.…”
Section: Discussionsupporting
confidence: 92%
“…Future studies should aim to improve the ability to deliver messages that are tailored, appropriate and acceptable to specific risk groups, especially in a setting such as Indonesia where sex outside marriage is heavily stigmatised and where sex between males is still illegal and considered a serious offence. 40,41 While this study clearly showed the feasibility of implementing an SMS intervention to deliver health messages to a cohort of young people in Indonesia, the recruitment locations and the face-to-face recruitment approach limited the total potential reach of the study and resulted in recruiting a more highly educated and lower risk profile than other nationally representative samples. 42,43 The 2017 Indonesian Demographic and Health Survey reported that almost 10% of unmarried women aged 15-24 years with no education have had sexual intercourse, which is higher than those who finished primary and higher education.…”
Section: Discussionmentioning
confidence: 91%
“…The qualitative data analysis framework by Ritchie and Spencer [ 28 , 29 ] was employed to analyse the data. This framework offereda systematic approach to manage the data and provided coherence and structure of analysis [ 30 32 ]. The data analysis followed five steps including: Familiarisation with the data through reading transcripts line by line repeatedly, breaking data into several chunks and commenting or labelling the data; Identifying key issues, concepts and themes in a coding frame and developing a coding scheme; Indexing the entire data by creating open coding where similar and redundant codes were identified and the list made smaller and manageable.…”
Section: Methodsmentioning
confidence: 99%